Genetic diversity and population structure of Dermatophagoides farinae based on microsatellite markers. Issue 4 (4th July 2022) - Li, Mengnan; Fang, Weixi; Wang, Huihui; Chen, Zijian; Li, Xingrong; Liu, Yi; Li, Yongqi; Wang, Duo; Huang, Qingyu; Lu, Wenyan; Han, Renrui; Hong, Liang; et al.
ABSTRACT: Dermatophagoides farinae is one of the most important allergens that cause allergic diseases and trigger serious harm to the human body. D.farinae is widely distributed, and the development of genetic markers and genetic information regarding the populations of this species are needed to establish control strategies. The aim is to develop a microsatellite marker and assess the genetic diversity and population structure of different populations of D. farinae. The genomic DNA of D. farinae was extracted and sequenced by NGS analysis. Microsatellite markers were identified and screened with MISA software. Primers were designed with Primer5.0 and screened by capillary electrophoresis detection. Genotyping was implemented with GeneMarker 2.2. Genetic diversity and population structure were analysed by related softwares. Twelve microsatellite markers detected 66 alleles in 256 individuals of D. farinae from 12 geographic populations. The average allele number (Na), effective allele number (Ne), observed heterozygosity (Ho), and expected heterozygosity (He) were 4.431, 2.610, 1.056 and 0.484, respectively. Genetic variation existed within populations and there was no correlation between geographic distance and genetic distance (Fst) (P = 0.160). Structure analysis showed D. farinae is largely divided into three groups. The genetic diversity of the geographical population of D. farinae is relatively high.